Anodic TiO2 nanotubes: A promising material for energy conversion and storage - Galstyan, Vardan; Macák, Jan; Djenizian, Thierry (Elsevier Science BV, 2022)
Self-organized TiO2 nanotube (TNT) layers formed by an anodization process have emerged for the conception of innovative systems in the conversion and storage of energy. Herein, the latest progress in power sources with a remarkable electrochemical performance involving these versatile nanomaterials is reported. Besides the key role of their physico-chemical properties, the significance of interfaces established with other materials to achieve the fabrication of batteries, supercapacitors and fuel cells showing high electrochemical performance is also high-lighted. Particularly, recent approaches based on the chemical modifications of the TNTs by doping, solid-state reactions, atomic layer deposition, electrodeposition of metallic nanoparticles and copolymers are presented. In addition, the strong potential offered by TNT layers for future research works is discussed. This progress report seeks to demonstrate the strong input of anodic TNT layers for developing the next generation of autonomous devices while stimulating more research efforts dedicated to modern technological applications.
Anodické nanotrubice TiO2: Slibný materiál pro přeměnu a skladování energie
Keywords: TiO(2 )nanotubes; nanostructured electrodes; Li-ion microbatteries; supercapacitors; fuel cells; TiO2 nanotrubice; nanostrukturované elektrody; Li-ion mikrobaterie; superkondenzátory; palivové články